2014
DOI: 10.1063/1.4892079
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent diffusion of ion-implanted silicon in In0.53Ga0.47As

Abstract: Hard x-ray photoelectron spectroscopy study of As and Ga out-diffusion in In0.53Ga0.47As/Al2O3 film systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Si is a predominant n-type dopant for III-As materials and historically has been reported to have limited diffusivity upon thermal processing [13,79,80]. More recent reports have shown that Si diffusion is highly concentration dependent [81,82]. Si concentrations above 1-3×10 -19 cm −3 are shown to diffuse very rapidly while Si concentrations below this range are generally immobile as shown in Fig.…”
Section: Si Diffusion Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Si is a predominant n-type dopant for III-As materials and historically has been reported to have limited diffusivity upon thermal processing [13,79,80]. More recent reports have shown that Si diffusion is highly concentration dependent [81,82]. Si concentrations above 1-3×10 -19 cm −3 are shown to diffuse very rapidly while Si concentrations below this range are generally immobile as shown in Fig.…”
Section: Si Diffusion Studiesmentioning
confidence: 86%
“…3. SIMS profiles of concentration-dependent diffusion observed for ion-implanted InGaAs upon (a) rapid thermal anneal and (b) furnace anneals at 750°C [81,102]. level increases toward the conduction band E c , the formation energy of negatively charged cation vacancies V III n− have been calculated to decrease in InGaAs and other III-As materials [18,19,[94][95][96][97].…”
Section: Dft Calculations Of Ingaas Systemmentioning
confidence: 99%
“…The presence of vacancy defects is also likely evidenced by the highly concentration dependent nature of Si diffusion in these substrates. 25,57 Silicon is believed to diffuse via a group III vacancy mechanism in InGaAs and GaAs and a large increase in the population of group III vacancies should enhance Si diffusion in InGaAs, as is observed at high doping concentrations. Previous studies of Si diffusion in InGaAs show that at high doping concentration above 2 Â 10 19 cm À3 where electrical activation is saturated, there is a significant amount of diffusion of Si despite Si being inactive at these concentrations, suggesting the presence of a mobile, yet electrically inactive Si III -V III complex.…”
Section: B Origins Of N-type Carrier Saturation In Ingaasmentioning
confidence: 98%
“…Previous implant studies have concluded that Si redistribution upon annealing is minimal but more recent reports have indicated that Si redistribution is heavily concentration dependent above 2 Â 10 19 cm À3 . 2,24,25 The post 5 s RTA Si concentration profiles were measured by SIMS for the highest (6 Â 10 14 cm À2 ) and lowest (3 Â 10 13 cm À2 ) Al þ and P þ co-implant doses and are shown in Fig. 3(a).…”
Section: B Si Diffusionmentioning
confidence: 99%
“…Si is generally reported to have limited diffusivity in InGaAs but more recent reports suggest that the diffusion of Si in InGaAs is actually heavily concentration dependent. 36 Historically, Si seems to be an attractive dopant for implantation and growth methods of incorporation while Se, Sn, and Te are likely best suited for growth based techniques due to implant damage considerations. Dopant activation.-N-type dopants in InGaAs may come from either group IV or group VI.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (5) Q12mentioning
confidence: 99%